COMPARISON OF CHANGE IN CENTRAL CORNEAL THICKNESS (CCT) IN PATIENTS OF PRIMARY OPEN ANGLE GLAUCOMA (POAG) ON PROSTAGLANDINS MONOTHERAPY, BETA BLOCKERS MONOTHERAPY AND CARBONIC ANHYDRASE INHIBITOR (CAI) - BETA BLOCKER COMBINATION THERAPY (The Research of Medical Science Review, 2024)
Background: The most prevalent type of glaucoma worldwide is the primary open angle glaucoma (POAG). It features progressive retinal ganglionic cell axons’ loss causing peripheral visual field loss initially and ultimately leading to irreversible blindness if left unmanaged. IOP is the only modifiable factor with proven effect in stopping glaucomatous damage. Objective: To compare the change in central corneal thickness (CCT) in patients of primary open angle glaucoma (POAG) on Prostaglandins monotherapy, beta blockers monotherapy and Carbonic Anhydrase Inhibitor (CAI) - Beta Blocker combination therapy. Materials And Methods: This quasi-experimental study was carried out at Institute of Ophthalmology Unit III, KEMU/Mayo Hospital, Lahore. The study was completed in 1 year after the approval of synopsis. Patients were started on prostaglandins monotherapy (latanoprost), beta blockers monotherapy (betagan) or CAI-beta blockers combination therapy (Co-dorzal) as per the need; placed in groups A, B and C respectively. CCT was measured before the start of therapy with the use of pachymeter. RESULTS: The results showed the mean age of all patients to be 51.65 ± 9.62 years with minimum and maximum age as 40 and 85 years. In this study there were 65(45.1%) male and 79(54.9%) female cases. At baseline, the mean CCT of the right side was 540.12 ± 4.10, 539.25 ± 3.35 and 538.98 ± 3.17 in the groups A, B and C respectively with no significant difference. On the left side, the mean CCT was 539.75 ± 3.43, 538.71 ± 2.47 and 538.98 ± 3.09 for groups A, B and C respectively with no significant difference. Conclusion: It is concluded that the mean change in central corneal thickness and IOP was statistically higher in group A ( prostaglandins monotherapy) patients as compared to group-B (beta-blockers) and group-C (beta-blockers and carbonic anhydrase inhibitors combination therapy) in primary open angle glaucoma patients. Hence in future the effect of drugs must be borne in mind when measuring IOP and the measurement be adjusted with repeated central corneal thickness measurements.